A kind of anti-hygroscopic inorganic phosphate binder curing agent for dry coated sand and its application
By using a curing agent of specific components in the dry-coated sand of inorganic phosphate binder, the problem of irritating odor and poor hygroscopicity of the sand during heating and curing molding is solved, and higher hygroscopicity and stability are achieved, and it is suitable for the preparation of cast sand molds.
Patent Information
- Application Number
- CN202211417589.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-11-11
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2042-11-11
AI Technical Summary
Inorganic phosphate binder dry-state coated sand has irritating odor problems during heating and curing and molding, and has poor hygroscopicity, which affects its application.
A curing agent for dry-state coated sand with anti-hygroscopic inorganic phosphate binder is adopted, including coupling agent, phosphate binder, hydrophilic silica, organic weak acid, magnesium citrate hydrate and sodium dihydrogen hydrate. After pre-mixing and adding coupling agent to the roasted sand, it is dried in hot air to remove moisture, and finally calcium stearate is added to improve hygroscopic resistance.
The hygroscopicity and stability of the dry-state coated sand of inorganic phosphate binder is improved, and the irritating odor during heating and curing is reduced. The method is low-carbon and environmentally friendly, has low cost and good fluidity, and is suitable for the preparation of cast sand molds.
Smart Images

Figure CN115889680B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of inorganic phosphate binder molding sand casting, and in particular to a curing agent for anti-hygroscopic inorganic phosphate binder dry coated sand and application thereof. Background Art
[0002] Inorganic phosphate binder dry coated sand is a new type of coated sand. Compared with the traditional coated sand with organic resin as binder, inorganic phosphate dry coated sand has good disintegration, does not contain organic matter, is non-toxic, and its biggest advantage is low carbon and environmental protection, and low cost. Compared with wet sand, it has excellent fluidity and other advantages, so its application prospects are very broad. However, the inorganic phosphate binder dry coated sand currently developed also has some shortcomings, such as poor moisture absorption resistance, defects in the coated sand manufacturing process and some key auxiliary materials, etc., which to a certain extent limit the application of inorganic phosphate sand.
[0003] Compared with traditional organic resin coated sand, the inorganic phosphate binder dry coated sand has the advantages of being non-toxic and environmentally friendly. However, in the patent document that has been consulted (CN202011376890.8), it was found that during heating and curing molding, the temperature of the sandblasting machine was too high, and certain auxiliary additives that play a special role, although the amount added is very small, will produce a pungent odor, which is not in line with the concept of green environmental protection. In addition, the performance is unstable and the moisture absorption resistance is poor, which is also a current problem.
[0004] To solve the above problems, the present invention is a method for improving the moisture absorption resistance of dry coated sand with inorganic phosphate binder, reducing irritation and improving stability. Summary of the invention
[0005] One of the purposes of the present invention is to provide a curing agent for inorganic phosphate binder dry coated sand with hygroscopic resistance, so as to solve the problem that the current inorganic phosphate binder dry coated sand has a pungent odor during heating and curing. And the problem that the current inorganic phosphate binder dry coated sand has poor hygroscopic resistance.
[0006] The second purpose of the present invention is to provide an application of a curing agent for dry coated sand with an anti-hygroscopic inorganic phosphate binder in the preparation of casting sand molds. A coupling agent is added to the roasted sand to mix the sand, and then a pre-mixture of a binder, hydrophilic silica, an organic weak acid aqueous solution, a hydrate and other materials are added separately to continue mixing the sand. Finally, hot air is passed through to dry the inorganic binder to remove moisture, and calcium stearate is added after screening. The purpose is to prevent the coated sand from absorbing moisture during storage on the one hand, and to promote the fluidity of the coated sand during sand shooting on the other hand.
[0007] A hygroscopic inorganic phosphate binder curing agent for dry coated sand, comprising the following components:
[0008] Coupling agent: 4 parts;
[0009] Phosphate binder: 20-30 parts;
[0010] Hydrophilic silica: 0.06-0.09 parts;
[0011] Organic weak acid: 8.3-14.6 parts;
[0012] Magnesium citrate hydrate: 25 parts;
[0013] Sodium dihydrogen phosphate hydrate: 5-20 parts;
[0014] Calcium stearate: 0.1 part;
[0015] The silane coupling agent is KH550, and the organic weak acid aqueous solution is a 1:2 citric acid aqueous solution.
[0016] The particle size of the hydrophilic silica is 20 nanometers.
[0017] Preferably, the magnesium citrate hydrate is magnesium citrate nonahydrate, and the sodium dihydrogen phosphate hydrate is sodium dihydrogen phosphate dihydrate.
[0018] Preferably, the magnesium citrate nonahydrate is in the form of granules with a particle size of ≥100 mesh, and the sodium dihydrogen phosphate dihydrate is in the form of granules with a particle size of ≥70 mesh.
[0019] Preferably, the composition of the phosphate binder is 56.170% industrial phosphoric acid, 12.879% aluminum hydroxide, 1.994% boric acid, 0.332% silicic acid, 0.831% magnesium oxide, 0.831% copper oxide, 0.042% yttrium oxide, 1.994% hydroxyethylidene diphosphonic acid, and 24.927% purified water.
[0020] In the above-mentioned coated sand formula, the role of magnesium citrate nonahydrate and sodium dihydrogen phosphate dihydrate is to react when the mold is heated to generate a non-water-soluble product of magnesium hydrogen phosphate to improve the resistance to moisture absorption, while releasing crystal water to re-moisten the dry binder film so that the sand particles form bonding bridges to each other, thereby having a certain strength.
[0021] At the same time, magnesium citrate nonahydrate and sodium dihydrogen phosphate dihydrate do not contain elements that may produce toxic or irritating gases, and will not emit toxic or irritating gases during heating, molding and application.
[0022] The solution adopted by the present invention to achieve the second purpose is: use of the anti-hygroscopic inorganic phosphate binder dry coated sand curing agent in the preparation of casting sand molds.
[0023] A coupling agent accounting for 0.4% by mass of the sand is added to the roasted sand to obtain a mixed sand, and then 2.0% to 3.0% by mass of an inorganic phosphate binder, 0.006% to 0.009% by mass of hydrophilic silicon dioxide, 0.83% to 1.46% by mass of an organic weak acid, 2.5% by mass of a magnesium citrate hydrate, and 0.5% to 2.0% by mass of a sodium dihydrogen phosphate hydrate are pre-mixed and homogenized, then added to the mixed sand and mixed continuously, and hot air is passed through to dry the mixture to remove moisture from the inorganic binder, and 0.01% by mass of calcium stearate is added to the mixture after screening, and the mixture is uniformly mixed to obtain dry coated sand; the finished coated sand is sprayed into a mold by a core shooting machine, and is heated and solidified and then demolded, and the heating temperature is 135° C., which is higher than the water loss temperature of the crystalline hydrate.
[0024] Preferably, the temperature of the hot air is 45±5°C.
[0025] Preferably, the inorganic phosphate binder, hydrophilic silica, organic weak acid, magnesium citrate hydrate, and sodium dihydrogen phosphate hydrate are pre-mixed and homogenized and remain effective within 6 hours.
[0026] Compared with the prior art, the present invention has the following beneficial effects:
[0027] 1. The anti-hygroscopic inorganic phosphate binder curing agent for dry coated sand provided by the present invention has the characteristics of good disintegration and non-toxicity when preparing casting sand molds, and the use process is low-carbon and environmentally friendly, low-cost, and has excellent fluidity compared with wet sand. The dry coated sand prepared by the curing agent has high anti-hygroscopicity after sand shooting and curing. At the same time, the binder film makes the sand particles bond to each other and have stable strength. The whole preparation curing speed is fast and the sand core bonding strength is high.
[0028] 2. After the curing agent for dry coated sand provided by the present invention is mixed evenly with dry sand, coated sand with uniform particle size is obtained by screening. When the mold is heated, magnesium citrate nonahydrate reacts with sodium dihydrogen phosphate dihydrate and the binder to generate a non-water-soluble product of magnesium hydrogen phosphate, so that the molecules in the original thermal curing product in the bonding bridge are all connected to form a bridge by "O" bonds, and now part of them are bridged by "Mg" bonds, because the "O" bond has a strong affinity with water molecules and is very easy to form hydrogen bonds with water molecules in the air, thereby destroying the bonding strength of the binder, while the "Mg" bond is not easy to combine with water molecules, thereby improving the anti-hygroscopicity. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 Infrared spectrum analysis diagram of infrared and laboratory analytical pure magnesium hydrogen phosphate trihydrate of the present invention. DETAILED DESCRIPTION
[0030] For a better understanding of the present invention, the following examples are provided to further illustrate the present invention, but the present invention is not limited to the following examples.
[0031] Example 1
[0032] A method for preparing a sand sample comprises the following steps:
[0033] 1. Weigh 1000g of raw sand and 4g of silane coupling agent for later use;
[0034] 2. Add raw sand and silane coupling agent into the mixer and stir for 60 seconds;
[0035] 3. Weigh and evenly mix 30 g of phosphate binder, 14.6 g of citric acid aqueous solution with a mass ratio of 1:2, 0.09 g of hydrophilic silicon dioxide, 25 g of magnesium citrate nonahydrate and 15 g of sodium dihydrogen phosphate dihydrate, and add them to the sand obtained in step 2 and continue mixing for 120 seconds;
[0036] 4. Place the wet sand obtained in step 3 in a hot air mixer, and introduce hot air at 45±5°C while stirring. When the sand particles in the mixer are evenly dispersed without obvious lumps, dry coated sand is obtained. After screening, seal and store for later use.
[0037] 5. Add 0.1g calcium stearate to the above dry coated sand and mix for 30 seconds;
[0038] 6. Use core shooting machine to shoot sand, mold temperature is 135℃, mold heating time is 3.5min, and solidification molding is performed;
[0039] 7. Open the mold, take out the sample and measure its tensile strength when it cools to room temperature.
[0040] The binder is composed of the following substances in percentage by weight: 56.170% industrial phosphoric acid, 12.879% aluminum hydroxide, 1.994% boric acid, 0.332% silicic acid, 0.831% magnesium oxide, 0.831% copper oxide, 0.042% yttrium oxide, 1.994% hydroxyethylidene diphosphonic acid, and 24.927% pure water. The mass fraction of the solute in the binder to the solution is greater than 60%, which is greater than the standard of olefinic acid and is a concentrated acid. Dilute acid generally refers to a solute mass fraction of the solution less than 20%.
[0041] Example 2
[0042] A method for preparing a sand sample comprises the following steps:
[0043] 1. Weigh 1000g of raw sand and 4g of silane coupling agent for later use;
[0044] 2. Add raw sand and silane coupling agent into the mixer and stir for 60 seconds;
[0045] 3. Weigh and evenly mix 25 g of phosphate binder, 12.5 g of citric acid aqueous solution with a mass ratio of 1:2, 0.075 g of hydrophilic silica, 25 g of magnesium citrate nonahydrate and 20 g of sodium dihydrogen phosphate dihydrate, add to the sand obtained in step 2 and continue mixing for 120 seconds;
[0046] 4. Place the wet sand obtained in step 3 in a hot air mixer, and introduce hot air at 45±5°C while stirring. When the sand particles in the mixer are evenly dispersed without obvious lumps, dry coated sand is obtained. After screening, seal and store for later use.
[0047] 5. Add 0.1g calcium stearate to the above dry coated sand and mix the sand for 30S;
[0048] 6. Use the core shooting machine to shoot sand, the mold temperature is 135℃, the mold heating time is 5min, and the solidification is completed;
[0049] 7. Open the mold, take out the sample and measure its tensile strength when it cools to room temperature.
[0050] Example 3
[0051] A method for preparing a sand sample comprises the following steps:
[0052] 1. Weigh 1000g of raw sand and 4g of silane coupling agent for later use;
[0053] 2. Add raw sand and silane coupling agent into the mixer and stir for 60 seconds;
[0054] 3. Weigh and evenly mix 20 g of phosphate binder, 8.3 g of citric acid aqueous solution with a mass ratio of 1:2, 0.06 g of hydrophilic silicon dioxide, 25 g of magnesium citrate nonahydrate and 5 g of sodium dihydrogen phosphate dihydrate, add to the sand prepared in step 2 and continue mixing for 120 seconds;
[0055] 4. Place the wet sand obtained in step 3 in a hot air mixer, and introduce hot air at 45±5°C while stirring. When the sand particles in the mixer are evenly dispersed without obvious lumps, dry coated sand is obtained. After screening, seal and store for later use.
[0056] 5. Add 0.1g calcium stearate to the above dry coated sand and mix the sand for 30S;
[0057] 6. Use core shooting machine to shoot sand, mold temperature is 135℃, mold heating time is 3.5min, and solidification molding is performed;
[0058] 7. Open the mold, take out the sample and measure its tensile strength when it cools to room temperature.
[0059] Comparative Example
[0060] A method for preparing a sand sample comprises the following steps:
[0061] 1. Weigh 1000g of raw sand, 4g of silane coupling agent, and 1g of magnesia powder for later use;
[0062] 2. Add raw sand and magnesia powder into the mixer and stir for 40 seconds;
[0063] 3. Add the molding sand and silane coupling agent in step 2 into the mixer and stir for 60 seconds;
[0064] 4. Weigh and evenly mix 25 g of phosphate binder, 0.075 g of hydrophilic silica, 4 g of citric acid aqueous solution with a mass ratio of 1:2, and 30 g of aluminum sulfate 18hydrate, then add to the sand obtained in step 3 and continue mixing for 120 seconds;
[0065] 5. Place the wet sand obtained in step 4 in a hot air mixer, and introduce hot air at 45±5°C while stirring. When the sand particles in the mixer are evenly dispersed without obvious lumps, dry coated sand is obtained. After screening, seal and store for later use.
[0066] 6. Add 0.1g calcium stearate to the above dry coated sand and mix the sand for 30S;
[0067] 7. Use core shooting machine to shoot sand, mold temperature is 150℃, mold heating time is 3.5min, and solidification is performed;
[0068] 8. Open the mold, take out the sample and measure its tensile strength when it cools to room temperature.
[0069] Experimental test results:
[0070] The molding sands prepared in Examples 1-3 of the present invention and the comparative example were used to make standard "8"-shaped samples using a core shooting machine. After the samples were demolded and cooled to room temperature, the tensile strength was measured according to the GB / T2684-2009 test method for casting sand and mixtures. The results are shown in the following table:
[0071]
[0072] From the data in the above table, it can be seen that the average tensile strength decrease rate of the samples prepared in Examples 1-3 of the present invention after 12 hours is significantly lower than that of the comparative example, that is, the moisture absorption resistance is significantly improved. Although the average tensile strength of Example 3 is lower, the average tensile strength decrease rate of the sample after 12 hours is the smallest. Overall, Example 1 is superior to other solutions, and the moisture absorption resistance of the embodiments is superior to that of the comparative example.
[0073] from Figure 1 It can be seen that by comparing the infrared spectrum of the reaction product of the mixture after high-temperature sandblasting of the present invention with the infrared spectrum of the analytically pure magnesium hydrogen phosphate trihydrate purchased in the laboratory, the -1 Up to 2000cm -1The trend of the spectrum is very similar within the wavelength range. The infrared spectrum of the present invention is at 1728cm -1 、1632cm -1 、1421cm -1 、1090cm -1 、892cm -1 、520cm -1 The absorption peak at 1702 cm -1 、1653cm -1 、1450cm -1 、1091cm -1 、888cm -1 、511cm -1 The positions of the absorption peaks are very close, so it can be considered that there is magnesium hydrogen phosphate in the reaction product of the mixture.
[0074] In the coated sand formula of the embodiment of the present invention, magnesium citrate nonahydrate and sodium dihydrogen phosphate dihydrate react when the mold is heated to generate a water-insoluble product of magnesium hydrogen phosphate to improve the anti-hygroscopicity, and at the same time release crystal water to re-moisten the dry binder film so that the sand particles form a bonding bridge to each other, thereby having a certain strength; in addition, the citrate in the magnesium citrate can be used as a chelating agent, which is easy to form a complex with a high-valence metal ion, and Al (3 +) is a high-valence ion, so the citrate in the magnesium citrate can form a complex with the aluminum ion in the binder, and as the above-mentioned coated sand system is acidic, its complexing ability is enhanced. The nonahydrated magnesium citrate reacts with the dihydrated sodium dihydrogen phosphate and the binder to form a non-water-soluble product of magnesium hydrogen phosphate, so that the molecules in the original thermal curing product in the bonding bridge are connected by "O" bonds to form bridges, and now part of them are bridged by "Mg" bonds. Because the "O" bond has a strong affinity with water molecules, it is very easy to form hydrogen bonds with water molecules in the air, thereby destroying the bonding strength of the binder, while the "Mg" bond is not easy to combine with water molecules, thereby improving the anti-hygroscopicity. Therefore, when magnesium citrate, sodium dihydrogen phosphate and phosphate binder are mixed together, the bonding bridge between the sand particles has a stable strength and further improves the anti-hygroscopicity.
[0075] At the same time, the discharge temperature of sodium dihydrogen phosphate dihydrate is 60°C, while the discharge temperature of magnesium citrate nonahydrate is 110°C. Therefore, in the coating process of step 4, magnesium citrate nonahydrate is crystalline, the mass fraction of the solute in the binder to the solution is greater than 60%, and the dissolution rate of magnesium citrate nonahydrate in the binder is very slow. After magnesium citrate nonahydrate is added to the binder, the binder becomes very viscous. Sodium dihydrogen phosphate dihydrate is acidic, and it absorbs heat when added to the binder, which makes the temperature of the whole system drop very low, and further slows down the dissolution of magnesium citrate nonahydrate and sodium dihydrogen phosphate dihydrate. Therefore, magnesium citrate nonahydrate and sodium dihydrogen phosphate dihydrate do not react during the coating process, so they can be stored for a long time after premixing.
[0076] After sandblasting, under high temperature conditions in the mold, sodium dihydrogen phosphate dihydrate and magnesium citrate nonahydrate are hydrolyzed in sequence, releasing more crystal water to form an olefinic acid solution. Magnesium citrate nonahydrate is soluble in dilute acid and does not release toxic or irritating gases. Due to the complexation of citric acid, magnesium citrate is evenly dispersed in the mixture. Magnesium citrate reacts with sodium dihydrogen phosphate to form a network magnesium bond. Magnesium sand reacts with phosphate binder to form a chain magnesium bond. The reaction of existing magnesium sand with phosphate binder forms a chain magnesium bond, and the distribution of reactants is also uneven.
[0077] The above is only a preferred embodiment of the present invention, which certainly cannot be used to limit the scope of rights of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and changes can be made without departing from the principle of the present invention, and these improvements and changes are also regarded as the protection scope of the present invention.
Claims
1. Application of a hygroscopic inorganic phosphate binder dry coated sand curing agent in the preparation of foundry sand molds, characterized in that: A coupling agent accounting for 0.4% by mass of the sand is added to the roasted sand to obtain a mixed sand, and then 2.0% to 3.0% by mass of an inorganic phosphate binder, 0.006% to 0.009% by mass of hydrophilic silicon dioxide, 0.83% to 1.46% by mass of an organic weak acid, 2.5% by mass of a magnesium citrate hydrate, and 0.5% to 2.0% by mass of a sodium dihydrogen phosphate hydrate are pre-mixed and homogenized, then added to the mixed sand and mixed continuously, and finally hot air is introduced to dry the inorganic binder to remove moisture, and 0.01% by mass of calcium stearate is added to the sand after screening, and the sand is mixed uniformly to obtain dry coated sand; the finished coated sand is sprayed into a mold by a core shooting machine, and is heated and cured and then demolded, and the heating temperature is 135° C., which is higher than the water loss temperature of the crystalline hydrate.
2. The use according to claim 1, characterized in that: The temperature of the hot air is 45±5°C.
3. The use according to claim 2, characterized in that: The inorganic phosphate binder, hydrophilic silicon dioxide, organic weak acid, magnesium citrate hydrate and sodium dihydrogen phosphate hydrate are still effective within 6 hours after being pre-mixed and homogenized.
Citation Information
Patent Citations
Curing agent for inorganic phosphate binder precoated sand and application thereof
CN112453314A
Water-soluble casting mold and method for manufacturing the same
CN1524644A